Residual Current Measurement using Helmholtz Coil Configuration with different Current Flow - Erwin Sutanto; Frangky Chandra; Eduardo Gonnelli; Suhariningsih Suhariningsih (Institute of Advanced Engineering and Science, 2018)
For leakage current safety, Residual Current Device (RCD) has been well known. The purpose of this work is to make the employment of low price components to measure residual current feasible and the Residual Current Device (RCD) must to be taken into account because it is a well known device for leakage current safety. For this purpose, experiments employing the Helmholtz Coil Configuration were performed with the different current flow. Furthermore, the residual current was formulated and simulated through the software Easy Java Simulation (EJS). The results showed that it is possible to move the magnet into different angles using leakage current with linear gradient as low as 0.382 degree/mA. Finally, it was proposed a way to increase the sensitivity and to reduce the hysteresis phenomenon.